Cross-Cultural Context in ELT in Nepal - Sharma, Rom Nath (Siddhajyoti Interdisciplinary Journal, 2024)
This study explored the teachers’ practices of English Language Teaching (ELT) in cross-cultural context. Two teachers teaching English at secondary level schools located at Kapilvastu Municipality, Kapilvastu District were interviewed through zoom meeting to excavate the findings. While teaching in the multi-cultural classroom, teacher participants experienced communication misunderstandings and misinterpretations of the meaning due to the cultural differences of the students. Teachers were in need of the trainings for developing their professionalism in teaching effectively to multicultural students and in multicultural classrooms. However, they were not being facilitated with any kind of multi-cultural students teaching trainings so that they could make their teaching more effective to the students from diverse cultural backgrounds and linguistic differences. The study revealed that teachers had to teach in diverse cultural classes, shared learning of culture was practised using contextualization method and linguistics chaos was dug out in meaning construction. English language teaching and learning were influenced by mother tongues, cultural differences and cultural domination.